Clearance of Hepatitis B e Antigen in Untreated Chronic Hepatitis B Virus Infection: A Systematic Review and Meta-analysis. (2nd May 2022) - Mohareb, Amir M; Liu, Anne F; Kim, Arthur Y; Coffie, Patrick A; Kouamé, Menan Gérard; Freedberg, Kenneth A; Boyd, Anders; Hyle, Emily P
Abstract: Background: In people with hepatitis B virus (HBV) infection, persistence of hepatitis B e antigen (HBeAg) is associated with clinical progression and need for treatment. HBeAg loss represents partial immune control and is a critical event in the natural history of chronic HBV. Methods: We conducted a systematic review and meta-analysis of cohort studies that report HBeAg loss among people with untreated chronic HBV. We evaluated HBeAg loss using a random-effects model and conducted subanalysis on region. Results: We screened 10 560 publications, performed 196 full-text analyses, and included 26 studies for meta-analysis. The pooled rate of HBeAg loss was 6.46/100 person-years (PYs) (95% confidence interval, 5.17–8.08). Meta-regression showed that older age of participants and studies in Europe were associated with higher rate of HBeAg loss. Rates per 100 PYs were 7.43 (95% confidence interval, 6.30–8.75; 1 study) in Africa, 3.24 (2.61–4.02; 1 study) in the Eastern Mediterranean, 13.67 (11.21–16.66; 4 studies) in Europe, 7.34 (4.61–11.70; 5 studies) in North America, and 5.53 (4.05–7.55; 15 studies) in the Western Pacific. Conclusions: Spontaneous HBeAg loss occurs at a rate of 6.46/100 PYs. Variations by region and age group may reflect epidemiological, immunological, or HBV genotype-related differences. Abstract : Spontaneous loss of hepatitis B e antigen (HBeAg) is an important milestone of chronic hepatitis B infection. In this systematic review and meta-analysis, we found that the incidence rate of spontaneous HBeAg loss varies by age and geographic region.